2022
DOI: 10.1002/alr.22997
|View full text |Cite
|
Sign up to set email alerts
|

Mental health burden of empty nose syndrome compared to chronic rhinosinusitis and chronic rhinitis

Abstract: Background Empty nose syndrome (ENS) is characterized by the paradoxical perception of nasal obstruction despite patent sinonasal anatomy after surgery. We investigated the relationship between ENS, and anxiety, depression, obsessive‐compulsive disorder, and somatic symptom disorder (SSD) compared to individuals with chronic rhinitis (CR) and chronic rhinosinusitis (CRS). Methods This cross‐sectional survey study compared ENS and CR and CRS patients. A total of 116 patients participated: 58 ENS patients from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated that anxiety and depression are prevalent comorbidities in patients with ENS [ 13 , 14 , 15 , 16 ]. Surgical reconstruction of the nasal cavity can reduce the airspace as well as the airflow in ENS patients and is effective in improving both nasal and psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that anxiety and depression are prevalent comorbidities in patients with ENS [ 13 , 14 , 15 , 16 ]. Surgical reconstruction of the nasal cavity can reduce the airspace as well as the airflow in ENS patients and is effective in improving both nasal and psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond physical symptoms, patients with ENS may carry significant psychological symptoms, including chronic fatigue, frustration, irritability, anger, anxiety, and depression [ 13 , 14 , 15 , 16 ]. Using a questionnaire investigation, our previous study showed that 51% of ENS patients experienced comorbid depression and 73% experienced comorbid anxiety [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms are most often referred as the presence of paradoxical nasal obstruction despite an objectively patent nasal cavity, a lack of airflow sensation, a feeling of suffocation, nasal dryness, and neuropathic pain [ 40 ]. The first line of management includes nasal moisturization and humidification, supportive therapies of concomitant medical conditions (e.g., panic, anxiety, and depression) [ 41 , 42 ], and surgery. Surgical treatment to augment the loss of turbinate volume with temporary fillers, synthetic implants, and autologous materials has been reported to be an effective method [ 38 , 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese versions of the Sino‐Nasal Outcome Test‐25 (SNOT‐25), ENS6Q, Beck Anxiety Inventory (BAI), and Beck Depression Inventory‐II (BDI‐II) were used to assess the severity of symptoms and psychological burden (depression and anxiety) before and after surgery 2,7,8 . Questionnaire surveys were completed by participants in person when returned to the clinic.…”
Section: Methodsmentioning
confidence: 99%